Kontribusi Monumental Umat Muslim terhadap Kemajuan Sains dan Teknologi - Arini Ayu Soleha; Amelia Eka Pratiwi; Anjely Juniarti; Alihan Satra (CV. ITTC INDONESIA, 2026)
This article examines the monumental works of Muslims in the fields of science and technology, particularly during the Islamic Golden Age from the 8th to the 14th century. Using a literature review method, this study explores the contributions of prominent Muslim scholars including Al-Khwarizmi, Ibn Sina, Ibn Al-Haytham, and Jabir ibn Hayyan. The findings reveal that these scholars produced landmark works such as Kitab Al-Jabr wa Al-Muqabalah in mathematics, Al-Qanun fi Al-Tibb in medicine, Kitab Al-Manazir in optics, and Kitab Al-Kimya in chemistry. These works not only advanced knowledge within the Islamic world but were also translated into Latin and became foundational references at European universities for centuries. The study concludes that Islamic civilization played a decisive role in preserving and advancing global scientific knowledge, and that the intellectual legacy of Muslim scholars remains highly relevant to the development of modern science.